Kinetics of hematoma expansion in murine warfarin-associated intracerebral hemorrhage - Illanes, Sergio; Zhou, Wei; Heiland, Sabine; Zorn, Markus; Veltkamp, Roland (Brain research, 2010)
Background and purpose - The burden of intracerebral hemorrhage associated with oral anticoagulants (OAC-ICH) is growing. However, little is known about the pathophysiology of W-ICH. Herein, we refine a mouse model of OAC-ICH using repetitive T2* MRI to describe kinetics of hematoma enlargement, and establish a benchside point of care INR assay (PoC) for assessment of anticoagulation. - Methods - C57/BL6 mice drank warfarin (0.4mg/kg/24h) in their water. ICH was induced by stereotactic injection of collagenase type VII (0.045U) into the left striatum. Hemorrhagic blood volume was quantified by MRI T2* images and on cryosections 48h after ICH induction. Kinetics of hematoma expansion were compared in strongly, moderately, and non-anticoagulated mice using repeated MRI T2* imaging. The PoC INR technique was validated against standard laboratory INR, and tail vein bleeding time (TVBT). - Results - PoC INR correlated with central laboratory measurements (r=0.989; p<0.0001) and with TVBT (r=0.982; p<0.0001). Hematoma volume was 21.2±6.7mm3 in heavily (PoC INR 4−5), 12.3±4.8 in moderately (INR 2−3), and 8.6±3.3 in non-anticoagulated mice (INR<1.2). Hematoma volume determined from cryosections and T2* MRI correlated well (r=0.922). Strength of anticoagulation was associated with neurologic outcome. Hematoma enlargement occurred mainly during the first 3h in anticoagulated mice. - Conclusions - PoC allows repeated benchside INR measurements in individual mice which reflect the level of anticoagulation. Stronger anticoagulation results in larger hematoma volumes. As hematoma enlargement occurs mainly during the first hours, potential hemostatic therapies should be tested early in this OAC-ICH model.
Gesehen am 06.06.2023